Land as a common resource: fostering rural social sustainability in the face of fragmentation and rural social sustainability in Bade, Yobe State, Nigeria - Abba, Saleh; Hassan, Yunusa; Bulama, Lawan (Revista Ciência Geográfica, 2024)
This study examines the impact of land fragmentation on rural sustainability in Bade Local Government Area, Yobe State, Nigeria. The goal of the research is to comprehend the extent and nature of land fragmentation in the area, assess its effects on rural sustainability indicators, and propose sustainable land use strategies. A cross-sectional research design was employed for this study, utilizing a questionnaire survey to gather qualitative and quantitative data. Descriptive statistics and a farm budget model were used to analyze farmers’ socio-economic characteristics, land fragmentation patterns, and indicators of rural sustainability. The study discover that a significant number of farmers possess land sizes between 2 and 4 hectares, indicating a high level of land fragmentation. The majority of farmers acquired land through either inheritance or purchase even though limited access to land is also observed due to rental and government allocation practices. This study highlights the importance of sustainable land use practices for rural sustainability. Addressing land fragmentation requires policy interventions that promote land consolidation and agricultural mechanization. Enhancing access to land and secure land tenure rights can attract investment and improve productivity. The study recommends policy interventions and support mechanisms to mitigate land fragmentation and foster sustainable rural development in the area. In conclusion, this study underscores the significance of sustainable land use practices in enhancing agricultural productivity, reducing poverty, and improving the well-being of rural communities.